Artificial Intelligence (AI) Dalam Pendidikan Islam: Peluang, Tantangan, Dan Etika Keislaman - Aulia Putri; Herlini Puspika Sari; Muhammad Suma Hafiz; Qonita Az Zahra (4, 2026)
The development of Artificial Intelligence (AI) has significantly influenced various fields of life, including the education sector. In the context of Islamic education, the use of AI provides new opportunities to improve the quality of learning through the availability of digital learning resources, the development of interactive learning media, and the implementation of more adaptive learning systems. However, the use of AI also presents several challenges, such as limited digital literacy among educators, the potential for overdependence on technology, and ethical issues related to the use of information. This article aims to analyze the opportunities, challenges, and Islamic ethical perspectives in the utilization of Artificial Intelligence in Islamic education. This study employs a qualitative approach using the library research method by collecting data from scientific journal articles, books, and relevant academic publications published within the last five years. The collected data were analyzed descriptively to identify concepts, research findings, and scholarly perspectives regarding the integration of AI in Islamic education. The results indicate that AI has significant potential to support innovation in Islamic education learning. However, its utilization should be accompanied by the strengthening of Islamic ethical values such as honesty, responsibility, and trustworthiness. Therefore, the integration of AI in Islamic education should not only focus on technological advancement but also emphasize moral and spiritual values. Abstrak Perkembangan Artificial Intelligence (AI) telah memberikan dampak yang signifikan terhadap berbagai bidang kehidupan, termasuk dalam dunia pendidikan. Dalam konteks pendidikan Islam, pemanfaatan AI membuka peluang baru dalam meningkatkan kualitas pembelajaran melalui penyediaan sumber belajar digital, pengembangan media pembelajaran interaktif, serta penerapan sistem pembelajaran yang lebih adaptif. Namun demikian, penggunaan AI juga menimbulkan berbagai tantangan, seperti keterbatasan literasi digital pendidik, potensi ketergantungan terhadap teknologi, serta persoalan etika dalam penggunaan informasi. Penelitian ini bertujuan untuk menganalisis peluang, tantangan, serta etika keislaman dalam pemanfaatan Artificial Intelligence dalam pendidikan Islam. Penelitian ini menggunakan pendekatan kualitatif dengan metode library research melalui pengumpulan data dari artikel jurnal ilmiah, buku, serta publikasi akademik yang relevan dalam lima tahun terakhir. Data yang diperoleh kemudian dianalisis secara deskriptif untuk mengidentifikasi konsep, temuan, serta pemikiran para ahli mengenai integrasi AI dalam pendidikan Islam. Hasil penelitian menunjukkan bahwa AI memiliki potensi besar dalam mendukung inovasi pembelajaran pendidikan Islam, namun pemanfaatannya perlu diimbangi dengan penguatan nilai-nilai etika keislaman seperti kejujuran, tanggung jawab, dan amanah. Oleh karena itu, integrasi AI dalam pendidikan Islam harus diarahkan pada pengembangan pembelajaran yang tidak hanya berbasis teknologi tetapi juga berlandaskan nilai moral dan spiritual.